The use of drugs from the viewpoint of identity words: The ego-ecological approach of the user’s psychosocial identity (Case studies) - Ρήγα Αναστασία-Βαλεντίνη; Σ. Τριανταφυλλίδου Σοφία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF